The Influence of Customer Experience and Brand Image on Repurchase Intention of Fore Coffee Consumers in Surabaya - Hafizhah, Izdihar Nisrina; Izaak, Wilma Cordelia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Coffee today no longer serves merely as a beverage to overcome drowsiness but has become part of people’s lifestyle. This study aims to analyze the influence of Customer Experience and Brand Image on the Repurchase Intention of Fore Coffee consumers in Surabaya. The research method used is a quantitative approach by distributing questionnaires to 120 respondents who are consumers of Fore Coffee in Surabaya. The sampling technique applied is non-probability sampling with a purposive sampling method. Data analysis was conducted using Partial Least Squares (PLS) based on Structural Equation Modeling (SEM) through the SmartPLS 4.0 application. The results show that the Customer Experience variable has a positive and significant effect on Repurchase Intention. Similarly, Brand Image also has a positive and significant effect on Repurchase Intention. These findings confirm that a good customer experience and a strong brand image can increase consumers' repurchase intention toward Fore Coffee.